“From misdiagnosis to precision medicine: strengthening pediatric neuro-oncology care in LMICs toward equitable pLGG outcomes” - Lorena V. Baroni; Nichoans B. George; Erin E. Crotty; Eric Bouffet; Mohamed S. Abdelbaki (Frontiers in Oncology, 2026)
Pediatric brain tumors—particularly pediatric low-grade gliomas (pLGG)—represent a major survivorship inequity between high-income countries (HICs) and low- and middle-income countries (LMICs). While pLGG is highly curable in optimal-resource settings, outcomes in LMICs remain suboptimal due to delays in diagnosis, limited neurosurgical capacity, restricted access to molecular testing, and significant variability in pathology accuracy and treatment accessibility. Data from international pathology review programs highlight a major diagnostic challenge: misclassification rates of 18–32% for pediatric CNS tumors, with discrepancies often driven by limited neuropathology expertise and lack of essential tools such as immunohistochemistry and molecular profiling. Studies from both global outreach networks and single-institution reviews consistently demonstrate that brain tumors account for the majority of major disagreements, and that molecular markers such as BRAF alterations and H3 mutations are critical for accurate diagnosis and risk stratification. These gaps directly affect treatment decisions and outcomes. At the same time, pLGG treatment paradigms are shifting with the development of oral targeted MAPK-pathway inhibitors, which deliver high response rates with favorable toxicity profiles. These agents hold unique promise for LMIC settings because they avoid the need for prolonged intravenous chemotherapy and reduce dependence on central lines and high-intensity supportive care. However, widespread adoption is limited by cost, regulatory barriers, absence from essential drug lists, and lack of molecular diagnostics required to select patients who would benefit most. This review synthesizes evidence from the evolving pLGG diagnostic and therapeutic landscape, and applies the Global Initiative for Childhood Cancer (GICC) CureAll framework to pediatric neuro-oncology care in LMICs. Key strategies include strengthening pathology accuracy through neuropathology partnerships, telepathology, and essential immunohistochemical/molecular panels; as well as integrating pLGG into national cancer control plans, enabling access to targeted therapies through differential pricing and pooled procurement, and building regional molecular diagnostic hubs. Together, these initiatives can reduce diagnostic errors, expand access to precision medicine, and move LMICs closer to equitable outcomes for children with pLGG.